Implementation Of Revenue Sharing System On Loading Workers In Islamic Economic Perspective At The Goods Terminal In Banda Aceh - Mahlel Mahlel Mahlel (ITB AAS INDONESIA Surakarta, 2022)
Study this aim for knowing application Revenue Sharing for workers demolish load goods in town band aceh. For knowing the data from the research process that has been done. method data collection used is type study qualitative descriptive that uses data in the form of results interview to owner truck, manager companies and workers demolish load. The application of the revenue sharing system is a system for results income clean without reduce burden costs. this system is a system of giving right job given by Mudarib to all group workers who do demolish load goods at the unloading terminal load goods in town Banda Aceh. Revenue Sharing is one of the to cooperate with contract Mudharabah. Application Principle Revenue sharing for give Justice to owner companies, managers and workers who do demolish load goods.